2020
DOI: 10.1111/bph.14891
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat and obesity as modulators of breast cancer risk: Focus on DNA methylation

Abstract: Breast cancer (BC) is the most common cancer and second leading cause of cancer mortality in women worldwide. Validated biomarkers enhance efforts for early detection and treatment, which reduce the risk of mortality. Epigenetic signatures have been suggested as good biomarkers for early detection, prognosis and targeted therapy of BC. Here, we highlight studies documenting the modifying effects of dietary fatty acids and obesity on BC biomarkers associated with DNA methylation. We focus our analysis on change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 145 publications
(340 reference statements)
0
17
0
Order By: Relevance
“…This study demonstrated that changes in dietary habits and other lifestyle factors were associated with DNA methylation changes [100]. In summary, DNA methylation biomarkers should be useful to monitor lifestyle interventions, and differentially methylated sites obesity-associated could serve as targets for BC prevention [101].…”
Section: Obesity and Body Mass Index (Bmi)mentioning
confidence: 73%
“…This study demonstrated that changes in dietary habits and other lifestyle factors were associated with DNA methylation changes [100]. In summary, DNA methylation biomarkers should be useful to monitor lifestyle interventions, and differentially methylated sites obesity-associated could serve as targets for BC prevention [101].…”
Section: Obesity and Body Mass Index (Bmi)mentioning
confidence: 73%
“…In this context, it was demonstrated that the methylation levels of ZNF577 were also observed in association with adiposity and menopausal status, and the direction of differences in methylation levels were inverse to that in expression of this gene in the blood leukocytes. Dietary habits are also a risk factor for developing cancer and obesity, as well as both factors were related to the regulation of the methylation profile (44)(45)(46). Thus, when the methylation levels of ZNF577 were evaluated according to the dietary habits, breast cancer patients who adhered to a Mediterranean diet and who specifically consumed higher amounts of vegetables, legumes, and fish showed the highest levels of methylation in ZNF577, independently of menopausal and obesity status.…”
Section: Discussionmentioning
confidence: 99%
“…Schwingshackl et al () introduce the field of nutrigenomics in relation to the Mediterranean diet, whereby nutritional agents can affect the genome of the host through a variety of mechanisms, including epigenetics and generation of long non‐coding RNAs. The topic is reinforced in other two review articles of this themed issue (Beetch et al, ; Donovan et al, ). Epigenetic changes wrought by environmental exposure and inflammation may underpin the global burden of chronic disease.…”
mentioning
confidence: 84%
“…Enough safety data have been collated to allow hydroxytyrosol to gain novel food status by EFSA. The effects of EVOO to modify the methylome in breast cancers is also explored by Donovan, Wren, Cenker, Selmin and Romagnolo (). The theme of polyphenols is continued by Man et al () in the context of the microbiota where the metagenomic effects of nutraceuticals are an emerging field.…”
mentioning
confidence: 99%